A novel process-linked assembly failure model for adhesively bonded composite structures. Issue 1 (2017) - Yazdani Nezhad, Hamed; Zhao, Yifan; Liddel, Paul D.; Marchante, Veronica; Roy, Rajkumar
Abstract: The globally growing market for polymer composites and their increasing use within aircraft structures has necessitated reliable bonding of composite laminates to prevent structural failure. However, knowledge behind the interaction between curing process parameters and the failure of polymer composite bonded joints is not keeping pace with the market. A novel nonlinear correlation analysis has been employed and applied to experimental data, to attentively quantify the effect of curing parameters on the failure of bonded composite assemblies. The materials (adherends and adhesive) and the bonding processes were selected from those used in assembly of composite aircraft structures.